Pengaruh Komite Audit Terhadap Kinerja Perusahaan Melalui Manajemen Laba sebagai Variabel Intervening - Mohammad Makhrus (Jurnal Akuntansi dan Keuangan Islam, 2013)
This study aimed to assess whether the presence of audit committees on Go Publiccompanies have a significant influence on company performance. And whether earningsmanagement as an intervening variable in effect. The research data was taken from theannual report in 2010, with a population of firms that go on the list of Islamic securities(DES) to sample as many as 31 companies and analyzed by regression analysis. Fromthe test results empirically prove that the audit committee did not significantly influencethe performance of the company, it is seen from the significant variables of the auditcommittee (KA) of 0.262 is greater than 0.05. Furthermore earnings management (DTACC)an intervening variable in part to the influence of the audit committee (KA) on theperformance of the company (Tobins-Q).